Enterprise risk management: A literature review and agenda for future research - Anton Gabriel Sorin; Anca Elena Afloarei Nucu (Journal of Risk and Financial Management, 2020)
The Enterprise Risk Management (ERM) process has heterogeneously developed across the world, although it represents a leading paradigm, supporting organizations to identify, evaluate, and manage risks at the enterprise level. Academics have studied the process, but there is no complete picture of the determinants and implications of such an integrated risk management process. Therefore, we present a systematic empirical literature review on ERM, based on a research protocol. The review highlights that the ERM literature can be divided into four general lines of research: the ERM adoption, the determinants of the ERM implementation, the effects of ERM adoption, and other aspects. In contrast to the richness of studies devoted to ERM engagement in small and medium-sized enterprises (SMEs), studies exploring ERM adoption in banks or insurance are relatively few. The literature review has revealed that the most frequently investigated effect of ERM is on firm performance. Little effort has been dedicated to the analysis of the effectiveness of ERM by its components and to institutional, individual, and organizational factors that affect ERM adoption. The study can serve as a starting point for scholars to explore research gaps related to ERM, while the practitioners can rely on the presented findings to identify the effects of the ERM implementation.
Keywords: 330; Enterprise Risk Management; research agenda; systematic review